2010
DOI: 10.1371/journal.pone.0013666
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Fragmentation Threshold Hypothesis: Regime Shifts in Biodiversity Across Fragmented Landscapes

Abstract: Ecological systems are vulnerable to irreversible change when key system properties are pushed over thresholds, resulting in the loss of resilience and the precipitation of a regime shift. Perhaps the most important of such properties in human-modified landscapes is the total amount of remnant native vegetation. In a seminal study Andrén proposed the existence of a fragmentation threshold in the total amount of remnant vegetation, below which landscape-scale connectivity is eroded and local species richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
487
2
63

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 535 publications
(606 citation statements)
references
References 59 publications
35
487
2
63
Order By: Relevance
“…Even forest fragments greater than 5,000 ha had only 7.2 species on average out of the original 18 species. Another study comparing the occurrence of 27 forest specialist small mammal species in three landscapes of 100 km 2 in the Atlantic forest in Brazil found that about half of the species persisted in the landscape with 30% forest cover, but only one species persisted in the landscape with 10% forest cover (43,44). This result is consistent with data for forest-inhabiting birds in Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Even forest fragments greater than 5,000 ha had only 7.2 species on average out of the original 18 species. Another study comparing the occurrence of 27 forest specialist small mammal species in three landscapes of 100 km 2 in the Atlantic forest in Brazil found that about half of the species persisted in the landscape with 30% forest cover, but only one species persisted in the landscape with 10% forest cover (43,44). This result is consistent with data for forest-inhabiting birds in Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Infection rates in ticks are largely "diluted" because the high host densities buffer drastic changes in B. burgdorferi sensu lato prevalence. A low connectivity rate for habitat patches is not always synonymous with low prevalence in ticks (32). The classification map of Europe must be regarded as the best explanation of the tick prevalence rates as an output of abiotic variables, and not as a map of risk for humans.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve these doubts, we recommend a landscape-scale approach in future research, with the inclusion of matrix structure and habitat amount in the analysis. Over larger spatial scales (Pardini et al 2010), the absence of patch size effects can also be related to the high level of deforestation in our study area (3% forest cover). To support this explanation, future studies should examine this relationship between patch size and trophic interactions along the regional gradient of landscape degradation.…”
Section: Hypothesis Of Bottom-upmentioning
confidence: 80%